2004
DOI: 10.1021/je049927v
|View full text |Cite
|
Sign up to set email alerts
|

Partial Molar Volumes and Viscosities of Some α-Amino Acids in Micellar Solutions of Sodium Caprylate

Abstract: Densities and viscosities of aqueous solutions of R-amino acids (glycine, DL-alanine, DL-R-amino-n-butyric acid, DL-R-valine, and DL-R-leucine) + sodium caprylate have been measured as a function of the concentrations of amino acid and sodium caprylate at 298.15 K. These data have been used to calculate apparent molar volumes and viscosity B coefficients of the amino acids. The standard partial molar volume V°2 ,φ and standard volumes of transfer ∆ t V°have been determined for the amino acids. It has been show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…In the previous work, 33 we found that values of V°m ,2 for a given amino acid in aqueous solutions of some sodium carboxylates (NaC 2 , NaC 4 , and NaC 6 ) almost increase linearly with increasing side chain length of the carboxylate anion. Based on this fact and the linear relations shown in eq 6, the values of V°m ,2 for the amino acids can be correlated with the concentration of sodium carboxylate (m s ), the number of carbon atom (n c ) in alkyl chain of the amino acids, and the number of carbon atom (n s ) in hydrocarbon chain of the carboxylate anions by…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In the previous work, 33 we found that values of V°m ,2 for a given amino acid in aqueous solutions of some sodium carboxylates (NaC 2 , NaC 4 , and NaC 6 ) almost increase linearly with increasing side chain length of the carboxylate anion. Based on this fact and the linear relations shown in eq 6, the values of V°m ,2 for the amino acids can be correlated with the concentration of sodium carboxylate (m s ), the number of carbon atom (n c ) in alkyl chain of the amino acids, and the number of carbon atom (n s ) in hydrocarbon chain of the carboxylate anions by…”
Section: Discussionmentioning
confidence: 75%
“…In the previous work, we found that values of V ° m,2 for a given amino acid in aqueous solutions of some sodium carboxylates (NaC 2 , NaC 4 , and NaC 6 ) almost increase linearly with increasing side chain length of the carboxylate anion. Based on this fact and the linear relations shown in eq 6, the values of V ° m,2 for the amino acids can be correlated with the concentration of sodium carboxylate ( m s ), the number of carbon atom ( n c ) in alkyl chain of the amino acids, and the number of carbon atom ( n s ) in hydrocarbon chain of the carboxylate anions by The parameters obtained by least-squares analysis are as follows: b 1 = 28.43 cm 3 ·mol -1 , b 2 = 1.455 cm 3 ·kg -1 ·mol -2 , b 3 = 15.96 cm 3 ·mol -1 , b 4 = 0.2634 cm 3 ·kg -1 ·mol -2 , b 5 = −0.5288 cm 3 ·kg -1 ·mol -2 , b 6 = −0.07970 cm 3 ·mol -1 , b 7 = 0.06651 cm 3 ·kg -1 ·mol -2 at 298.15 K; and b 1 = 28.59 cm 3 ·mol -1 , b 2 = 1.475 cm 3 ·kg -1 ·mol -2 , b 3 = 16.10 cm 3 ·mol -1 , b 4 = 0.2447 cm 3 ·kg -1 ·mol -2 , b 5 = −0.4887 cm 3 ·kg -1 ·mol -2 , b 6 = −0.08744 cm 3 ·mol -1 , b 7 = 0.07152 cm 3 ·kg -1 ·mol -2 at 308.15 K. The standard deviations of the fit are 0.59 at (298.15 and 308.15) K. This empirical equation can be used to calculate V ° m,2 values of the amino acids studied in aqueous NaC 2 , NaC 4 , and NaC 6 solutions within a certain concentration (<2.0 mol·kg -1 ) of sodium carboxylates.…”
Section: Discussionmentioning
confidence: 87%
“…From the literature survey, we found that in recent years there are extensive studies of volumetric properties of amino acids in aqueous solution and in mixed aqueous solutions, and the protonation constant study of amino acids in mixed aqueous solution, but very few studies have been done in aqueous saccharide solutions. …”
Section: Introductionmentioning
confidence: 99%
“…4 Therefore, in living systems, carbohydrate and protein interactions play an important role in various biochemical processes such as immunology, biosynthesis, pharmacology, and medicine. 5 From the literature survey, we found that in recent years there are extensive studies of volumetric properties of amino acids in aqueous solution [6][7][8][9][10][11][12] and in mixed aqueous solutions, [13][14][15][16][17][18][19][20][21][22][23][24][25] and the protonation constant study of amino acids in mixed aqueous solution, [26][27][28][29] but very few studies have been done in aqueous saccharide solutions. [30][31][32][33][34][35][36] Amino acids (2-aminopropanoic acid, 2-amino-3-methylbutanoic acid, 2-amino-4-methylpentanoic acid, and 2-amino-3phenylpropanoic acid) are hydrophobic in nature.…”
Section: ' Introductionmentioning
confidence: 99%
“…Remarkable experimental work has been reported on the thermodynamic and transport properties of amino acids in aqueous salt solutions [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], but very few studies exist on the volumetric and transport properties of amino acids in aqueous organic salt solutions [24][25][26][27][28][29][30][31], probably due to the complex nature of their interactions. Moreover, no systematic studies are available on the thermodynamic and transport properties of amino acids having polar side group (chain) in the presence of organic salt solutions.…”
Section: Introductionmentioning
confidence: 99%